Sepia pharaonis Ink Mitigates Dehydroepiandrosterone-Induced Insulin Resistance in Mouse Model of Polycystic Ovarian Syndrome - Prathyusha Yamarthi; Rama Satyasri Kotipalli; Samatasai Patnaik; Kv Veena; Muralidharan Kathirvel; Rajkumar Vutukuri; Manjula Bhanoori (Pathophysiology, 2024)
The present study aims to evaluate the effect of Sepia pharaonis ink on insulin resistance in PCOS-induced mice. Treatment with sepia ink in dehydroepiandrosterone (DHEA)-induced PCOS mice at various doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg body weight mitigated the insulin resistance in the study groups with decreased concentration of testosterone and increased concentrations of estrogen and progesterone compared to the PCOS group tested by ELISA. The histopathological analysis and restoration of glucose analysis showed a significant reduction in treatment groups. Reduced expression of insulin resistance genes like androgen receptor (AR), insulin receptor substrate 1 (IRS-1), and insulin-like growth factor1 (IGF-1) by qRT-PCR indicate a positive impact of sepia ink in alleviating the symptoms associated with PCOS. Taken together, the results of this study indicate sepia ink as a promising therapeutic intervention and a possible drug target for insulin resistance in diabetes and gynecological disorders like PCOS.